2017
DOI: 10.1113/ep086441
|View full text |Cite
|
Sign up to set email alerts
|

One session of remote ischemic preconditioning does not improve vascular function in acute normobaric and chronic hypobaric hypoxia

Abstract: What is the central question of this study? It is suggested that remote ischemic preconditioning (RIPC) might offer protection against ischaemia-reperfusion injuries, but the utility of RIPC in high-altitude settings remains unclear. What is the main finding and its importance? We found that RIPC offers no vascular protection relative to pulmonary artery pressure or peripheral endothelial function during acute, normobaric hypoxia and at high altitude in young, healthy adults. However, peripheral chemosensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…Finally, RIPC did not impact cerebrovascular reactivity to inhalation of 5% CO 2 compared to the sham condition. To our knowledge, there is only one directly relevant study that assessed RIPC and cerebrovascular function in humans (Rieger et al 2017). In this study the authors measured cerebral blood flow responses to acute and chronic hypoxia, and found no effect of RIPC compared to controls, findings consistent with the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, RIPC did not impact cerebrovascular reactivity to inhalation of 5% CO 2 compared to the sham condition. To our knowledge, there is only one directly relevant study that assessed RIPC and cerebrovascular function in humans (Rieger et al 2017). In this study the authors measured cerebral blood flow responses to acute and chronic hypoxia, and found no effect of RIPC compared to controls, findings consistent with the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Although positive effects of IPC on peripheral blood vessels have been demonstrated (9), our results suggest that IPC does not affect ICA during prolonged sitting. In two very recent studies, IPC was also found not to alter cerebral blood flow when measured at the MCA during a short period of sitting (3) or at the ICA in the supine position (20). Our data, supported by these recent studies, therefore suggest that IPC unlikely alters blood flow in centrally located arteries, a finding that contrasts with peripheral arteries.…”
Section: Discussionsupporting
confidence: 85%
“…Repeated bouts of ischemia followed by reperfusion, known as ischemic preconditioning (IPC), seem to have a capacity to prevent or attenuate ischemia-induced vascular function in peripheral arteries (9). These protective effects of IPC may also be present in cerebral arteries (21), although some studies report mixed findings (3,20). Related to the metabolic pathway, a previous study in animals found that IPC alters AMP-activated protein kinase activity in the mitochondria, potentially contributing to improved regulation of glucose metabolism (17).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 15 min of severe isocapnic hypoxia (end‐tidal partial pressure of O 2 = 45 mmHg; equivalent to ∼5000 m) did not reduce endothelial function in healthy adults (Rieger et al . ). The latter study suggests that 15 min of hypoxia exposure may not be enough to elicit a reduction in endothelial function.…”
Section: Hypoxia and Endothelial Function In Lowlandersmentioning
confidence: 97%
“…Although the mechanism(s) responsible for the observed decline in shear stress during acute hypoxia remain unknown, these authors attributed it to heightened sympathetic vascular constraint (Weisbrod et al 2001). In contrast, 15 min of severe isocapnic hypoxia (end-tidal partial pressure of O 2 = 45 mmHg; equivalent to ß5000 m) did not reduce endothelial function in healthy adults (Rieger et al 2017). The latter study suggests that 15 min of hypoxia exposure may not be enough to elicit a reduction in endothelial function.…”
Section: Studies In Acute Hypoxia (Laboratory)mentioning
confidence: 98%